A frequency reconfigurable high‐order mode monopole antenna with two independently controlled band. Issue 10 (21st July 2022) - Luo, Yu; Zhao, Songjiang; Yan, Ningning; An, Wenxing; Ma, Kaixue
Abstract: A dual‐band printed monopole antenna with frequency‐independent reconfiguration is proposed. Two varactor diodes are placed at the zero point of the current distribution in the third‐ and fifth‐order modes of the traditional monopole radiator. By separately regulating the reverse bias voltage of the two varactor diodes, the corresponding two frequency bands can be controlled independently. A fully functional prototype is fabricated and characterized, which exhibits a continuously dual frequency‐tunable characteristic. The designed antenna has a simple structure and compact size of 98 × 40 mm 2 . The antenna can be used in multi radio wireless systems, which has a good potential for use in cognitive radio.